PENGARUH MODEL PEMBELAJARAN PREDICT-OBSERVE-EXPLAINE (POE) TERHADAP HASIL BELAJAR IPA SD ADVENT 3 MEDAN - Simbolon, Dedi Holden; Tambunan, Doni Douglas; Umangge, Iganus (Jurnal Ilmiah Aquinas, 2025)
This study aims to examine the effect of the Predict-Observe-Explain (POE) learning model on science learning outcomes of students at SD Advent 3 Medan. The research employed a quantitative approach using a quasi-experimental one-group pretest-posttest design. The sample consisted of 37 students selected through total sampling. The research instrument was a multiple-choice test comprising 25 questions, which had been previously validated and tested for reliability. Data analysis showed a significant improvement in students’ learning outcomes after the implementation of the POE model, with the average pretest score increasing from 28.00 to 57.41 in the posttest. A paired sample t-test yielded a significance value (p) of 0.000 (p < 0.05), indicating a statistically significant difference between pretest and posttest scores. The normalized gain score of 0.40 suggests a moderate level of effectiveness. These findings demonstrate that the POE model is effective in enhancing science learning outcomes and aligns with active, constructivist learning principles, supporting the “Merdeka Belajar” (Independent Learning) policy framework in Indonesia.